PENERIMAAN DIRI PADA PEMBANTU RUMAH TANGGA - Subhan Ajrin (Kafa`ah: Journal of Gender Studies, 2016)
PRT (housemaid) is a group of professional maids who exits with large number. Meanwhile, they sometimes were treated unfair by their households. The role of a PRT in the household becomes very important, when the family began to shift from domestic functions to public functions. The current condition shows that in the development process, poor women have disadvantage both economically and socially. They were trapped in a process that tends to be marginalized, co-opt and exploited them. In the relationship with self-acceptance PRT in undergoing work, they still looked down on this profession (PRT job is considered low because of work-related domestic/household), as well as someone who is considered abnormal conditions in the community. In other words, someone is considered 'abnormal' in the community can accept ourselves fully without feeling embarrassed with the environment, even though the get a lot of opposition from the neighborhood where it is located.